Penerapan Media Chat GPT pada Pembelajaran Manajemen Pendidikan terhadap Kemandirian Mahasiswa - Hary Murcahyanto (Universitas Hamzanwadi, 2023)
The development of digital technology, especially Artificial Intelligence at this time has grown very rapidly and has penetrated into learning technology. One of them is the development of Chat GPT which has begun to be widely used by students and affects the level of student independence. This study aims to examine the effect of the application of Chat GPT on learning education management on student independence. The research method used is a quantitative experiment with One-Group Pre-test and Post-test Design. The population was 40 people and all of them became samples. Data collection techniques are observation and documentation. Data instruments use validity sheets, observation sheets, and documentation. The analysis techniques used are Validity Test, observation data analysis, Prerequisite Test, and Hypothesis Test. The results showed that the application of Chat GPT in learning educational management significantly influenced student independence. In the pre-test, student independence is still in the category of starting to be independent, while in the post-test, student independence increases to be very independent. So, it is concluded that student independence can be increased by the application of Chat GPT in learning education management.